2023
DOI: 10.22541/essoar.167415214.45806648/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive analysis of the NOAA National Water Model: A call for heterogeneous formulations and diagnostic model selection

Abstract: With an increasing number of continental-scale hydrologic models, the ability to evaluate performance is key to understanding uncertainty in prediction and making improvements to the model(s). In 2016, the NOAA National Water Model (NWM) was put into operations to improve the spatial and temporal resolution of hydrologic prediction in the U.S. Here, we evaluate the NWM 2.0 historical streamflow record in natural and controlled basins using the Nash Sutcliffe Efficiency metric decomposed into relative error, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…They also found basin characteristics such as total contributing drainage area and path length also influence the NWM performance. Further, variables indicating anthropogenic activities -percent imperviousness and upstream storage in dams-also influence the bias and NSE in predicting the flood flows (Johnson et al, 2023). This indicates that the NWM performance depends on basin and hydroclimatic information, thereby exhibiting a regional/spatial error structure in predicting flood flows.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…They also found basin characteristics such as total contributing drainage area and path length also influence the NWM performance. Further, variables indicating anthropogenic activities -percent imperviousness and upstream storage in dams-also influence the bias and NSE in predicting the flood flows (Johnson et al, 2023). This indicates that the NWM performance depends on basin and hydroclimatic information, thereby exhibiting a regional/spatial error structure in predicting flood flows.…”
Section: Introductionmentioning
confidence: 97%
“…Continental-scale hydrology studies have evaluated parsimonious mechanistic models (Archfield et al, 2015), lumped-hydrological models , and hybrid (statistical-mechanistic) models for estimating streamflow at different time scales (Evenson et al, 2021). Utilizing distributed hydrological models provide a viable alternative to estimating daily streamflow at ungauged locations, but challenges remain in accurately predicting streamflow over continental scale (Johnson et al, 2023). Frame et al (2021) evaluated the National Water Model (NWM) for selected virgin basins and found that the performance of NWM is poorer compared to the post-processing models.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations